Pubertal induction in adolescents with DMD is associated with high satisfaction, gonadotropin release and increased muscle contractile surface area. Issue 1 (January 2021) - Wood, Claire L; Hollingsworth, Kieren G; Hughes, Eric; Punniyakodi, Sadhanandham; Muni-Lofra, Robert; Mayhew, Anna; Mitchell, Rod T; Guglieri, Michela; Cheetham, Timothy D; Straub, Volker
Abstract : Background: Pharmacological doses of glucocorticoids (GC) reduce inflammation and preserve muscle function in boys with Duchenne muscular dystrophy (DMD). Delayed puberty and bone fragility are consequences of GC treatment. The aim of this study was to determine the acceptability of a 2-year pubertal induction regimen using 4-weekly testosterone injections and examine changes in physique, bone integrity, muscle pathology (assessed by MRI) and muscle function. Methods: Fifteen prepubertal males with DMD, aged 12–17 years and receiving GC, were treated with an incremental testosterone regimen for 2 years. Participants completed a Treatment Satisfaction Questionnaire (TSQM). Data on BMI, bone density, muscle pathology and function were collected at baseline and 2 years later. Results: Testosterone injections were well tolerated, with high TSQM scores. Baseline BMI z-score was 2.16 (0.90) and 1.64 (1.35) 2 years later. Median testosterone levels were 9.7 nmol/L (IQR: 5.7–11.1) 6–9 months after the last injection with an associated increase in testicular volume. Lumbar spine z-score was 0.22 (s.d. 2.21) at baseline and 0.35 (s.d. 2.21) after 2 years. Upper and lower limb muscle contractile cross-sectional area increased in all participants during the trial ( P = 0.05 and P < 0.01, respectively). There was a reduction in T2 relaxation times in most muscle groups with stable upper limb muscle function. Conclusion: Incremental monthly testosterone injections were well tolerated, promoted endogenous testosterone production and had a positive impact on the skeleton and contractile muscle bulk with evidence suggesting a beneficial impact on the underlying disease process.